2022
DOI: 10.3390/su142214708
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumer Adoption of Mobile Banking: Extending the UTAUT2 Model with Proactive Personality

Abstract: Mobile banking is an innovative solution for improving financial inclusion; however, the use of this technology is still very limited in developing countries. Consequently, this study aims to investigate elements affecting mobile banking adoption in a developing country context by applying the well-known Unified Theory of Acceptance and Use of Technology two (UTAUT2) model. Since most existing investigations on mobile banking using the UTAUT2 neglect the effects of personality traits, this investigation extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 161 publications
1
5
0
Order By: Relevance
“…The results of the study, hedonic motivation does not have an influence on behavioral intention when using mobile banking services in Jabodetabek. These findings are in line with the conclusions of the study by Hilal and Varela-Neira (2022) in Lebanon, which demonstrated that hedonic motivation does not affect customer banking behavior intentions in Lebanon.…”
Section: The Influence Of Hedonic Motivation On Behavioral Intentionsupporting
confidence: 92%
“…The results of the study, hedonic motivation does not have an influence on behavioral intention when using mobile banking services in Jabodetabek. These findings are in line with the conclusions of the study by Hilal and Varela-Neira (2022) in Lebanon, which demonstrated that hedonic motivation does not affect customer banking behavior intentions in Lebanon.…”
Section: The Influence Of Hedonic Motivation On Behavioral Intentionsupporting
confidence: 92%
“…The UTAUT2 paradigm is far more pertinent when considering individual consumers and how well they accept technology while using it to access internet services. The adoption of mobile FinTech [30], mobile banking [31], and mobile payment [32] [27], [28], for example, have all been found to be better explained by the UTAUT2 model, which connects a variety of technological and behavioral elements. This investigation follows the DL&ML model, the TAM, and UTAUT2 [33] theories as the conceptual model for examining the student adoption of video recordings within the subject Introduction to Databases Practicum course.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding individual users and how they accept using technology to access online services, the UTAUT2 paradigm is more pertinent. The UTAUT2 model connects numerous discoveries that social commerce, technological, and behavioral aspects have the greater explanatory capacity for predicting use behavior [9], such as the acceptance of mobile payment [27]- [30], m-commerce [31], metaverse [32], [33], travel tracking mobile application [34], mobile finTech service [35], health information application [36]- [38], and online mobile banking [39], [40].…”
Section: Methodsmentioning
confidence: 99%